1997
DOI: 10.1038/bjc.1997.502
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of early squamous cell carcinoma with tetra(m-hydroxyphenyl)chlorin: optimal drug-light interval

Abstract: Summary The optimal drug-light interval for effective photodynamic therapy (PDT) of early squamous cell carcinomas was evaluated with tetra(m-hydroxyphenyl)chlorin (mTHPC) by means of two complementary modalities: irradiation tests and ex vivo fluorescence microscopy. A Syrian hamster cheek pouch tumour model was used in these experiments. Photodynamic therapy on both tumour-bearing and contralateral healthy cheek pouch mucosae was performed at 650 nm and 514 nm. Light doses of 12 J cm-2 were delivered at a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…At 24 h, strong fluorescence was seen in the cytoplasm of tumour cells, but not in the surrounding muscle cells. Results from studies using a Syrian hamster cheek pouch tumour model (Andrejevic-Blant et al, 1997) demonstrated high fluorescence levels in endothelial cells at 8 h after Foscan, with accumulation in squamous epithelial tissues from 2 to 4 days. Clinical studies in a group of patients treated with Foscan PDT for gynaecological cancers (Wierrani et al, 1997) or SCC of the upper airways (Andrejevic Blant et al, 2001) also demonstrated high fluorescence levels in endothelial and inflammatory cells during the first 20 h.…”
Section: Discussionmentioning
confidence: 99%
“…At 24 h, strong fluorescence was seen in the cytoplasm of tumour cells, but not in the surrounding muscle cells. Results from studies using a Syrian hamster cheek pouch tumour model (Andrejevic-Blant et al, 1997) demonstrated high fluorescence levels in endothelial cells at 8 h after Foscan, with accumulation in squamous epithelial tissues from 2 to 4 days. Clinical studies in a group of patients treated with Foscan PDT for gynaecological cancers (Wierrani et al, 1997) or SCC of the upper airways (Andrejevic Blant et al, 2001) also demonstrated high fluorescence levels in endothelial and inflammatory cells during the first 20 h.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in contrast to other PSs such as mTHPC, which provide a contrast in favour of the epithelial tissue at long DLI (450 h). It should be noted that this 50-h DLI is much longer than those considered in the present study (Andrejevic-Blant et al, 1997a.…”
Section: Discussionmentioning
confidence: 50%
“…In order to evaluate the depth and extent of the PDT treatment, we used a tissue damage scale graded from 0 to 4. The scaling is based on the lateral extension of the macroscopic necrosis, the formation of fibrin and the in-depth extension of the necrosis to the different mucosal layers after histological examination of the tissues sections, in a similar way to the previous studies with different PSs (Andrejevic-Blant et al, 1997a, Rosenbach-Belkin et al, 1998Zellweger et al, 2000). Histologically, the tissue damage scale is related with the number of layers of tissue that are necrosed as well as the lateral extension of the necrosis.…”
Section: Evaluation Of the Photodynamic Effectmentioning
confidence: 92%
See 1 more Smart Citation
“…We consider that rapid and cancer-selective PS delivery by HVJ-E allowed selective accumulation of the PS even at a short incubation period [24] [25]. Based on this, we performed PDT using PE with high con- In this study, we also evaluated the selectivity of cell death induced by PDT using PE with the 10 min drug-light interval.…”
Section: Discussionmentioning
confidence: 99%